Simulation Of Mixed Convective Heat Transfer Using Lattice Boltzmann Method - A. R. M., Rosdzimin; S. M., Zuhairi; C. S. N., Azwadi (Universiti Malaysia Pahang, 2010)
In this paper, mixed (forced–natural) convective heat transfer around a heated square cylinder located inside a lid driven cavity has been studied numerically using the lattice Boltzmann method in the range of 100≤ Re ≤ 1000 with the corresponding Richardson number 0.01≤Ri≤10. The double-population lattice Boltzmann formulation is used as the governing equation. Two dimensional nine-velocity models are used for thecomputation of the velocity field while a four-velocity model is used for the computation of the temperature field. We found that the combination of nine- and fourvelocity models can be applied to the calculation without losing its accuracy. The results are presented in the form of streamline and isotherm plots as well as the variation of local Nusselt number at the top surface of the heated square. The computational results demonstrate that the flow pattern, formation of vortex and also the Nusselt number are influence by the Reynolds number and Richardson number